The Analysis of Internship (PPL) Implementation and Students Interest in Becoming a Teacher - Tika Muslihah Fauziah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2016)
The main focus of this study is to describe the implementation of Internship (PPL), the students’ interest in becoming a teacher, and whether the implementation of PPL program can increase of the interest of students to be a teacher. The research approach in this study is qualitative descriptive approach with the subjects of the research is the supervisor of the PPL program, counselor teacher, head of curriculum and students of Office Administration Education in the academic year of 2012 who have conducted PPL program. The research finding showed that: (1) PPL program has already performing quite well, it is due to the fact that it can provide benefits for students before becoming a teacher. However, there are still some obstacles and things that should be evaluated to ensure that PPL program can be ran effectively and efficiently, (2) the interest of students to become a teacher is influenced by various factors, internal and external, and (3) based on the interview result, the implementation of PPL program can increase of the interest of students to become a teacher.